The Minimum Number of Ablation Lines for Complete Isolation of the Pulmonary Veins during Thoracoscopic Ablation for Atrial Fibrillation - Min Suk Choi; Yoonseo Lee; Dong Seop Jeong (Life, 2023)
Total thoracoscopic ablation has been recommended as a class IIa indication for atrial fibrillation. However, the optimal number of ablation lines for pulmonary vein isolation has not yet been proposed. This study aimed to report the minimum number of ablation lines required to achieve an intraoperative conduction block. This study included a total of 20 patients who underwent total thoracoscopic ablation from December 2020 to July 2021. The epicardial conduction block was checked after each ablation line of pulmonary vein antral clamping. The median age was 61 years old. The median duration of atrial fibrillation since the first diagnosis was 78 months. Pulmonary vein isolation with bidirectional conduction block was confirmed in 90% of patients. A median of six ablation lines around each pulmonary vein antrum were performed according to our protocol even after the conduction block was verified. The median number of ablations to achieve an exit block was two on the right side and 3.5 on the left side. We found that most conduction blocks were achieved within three ablations around the pulmonary vein antrum. Our results may provide evidence to reduce the number of unnecessary ablation lines in the future.